2022
DOI: 10.1016/j.jneuroim.2021.577784
|View full text |Cite
|
Sign up to set email alerts
|

Stellate ganglion block reduces symptoms of Long COVID: A case series

Abstract: After recovering from COVID-19, a significant proportion of symptomatic and asymptomatic individuals develop Long COVID. Fatigue, orthostatic intolerance, brain fog, anosmia, and ageusia/dysgeusia in Long COVID resemble “sickness behavior,” the autonomic nervous system response to pro-inflammatory cytokines ( Dantzer et al., 2008 ). Aberrant network adaptation to sympathetic/parasympathetic imbalance is expected to produce long-standing dysautonomia. Cervical sympathetic chain activity c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
72
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(92 citation statements)
references
References 32 publications
1
72
0
2
Order By: Relevance
“…In this context review and further study of empirical or anecdotally successful ME/CFS therapies that target glia, such as minocycline ( Plane et al, 2010 ; Miwa, 2021 ; Numata, 2021 ), aripiprazole ( Segnitz et al, 2009 ; Yoneyama et al, 2014 ; Crosby et al, 2021 ), low dose naltrexone ( Cabanas et al, 2021 ), ketogenic diet ( Cossington et al, 2019 ), ketamine ( Chang et al, 2009 ), vagal stimulation ( Clancy et al, 2014 ; Meneses et al, 2016 ; Rodriguez et al, 2020 ; Namgung et al, 2022 ), and noninvasive transcranial neurostimulation ( Gómez et al, 2021 ; Sabel et al, 2021 ; Workman et al, 2021 ) may be informative. Therapies that indirectly affect the innate CNS immune response, including staphylococcal vaccine ( Zachrisson et al, 2002 , 2004 ), Bacillus Calmette–Guérin (BCG) vaccine ( Blok et al, 2015 ; Sánchez-Ramón et al, 2018 ), rintatolimod ( Strayer et al, 2020 ) and stellate ganglion block should also be considered ( Lipov et al, 2020 ; Liu and Duricka, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…In this context review and further study of empirical or anecdotally successful ME/CFS therapies that target glia, such as minocycline ( Plane et al, 2010 ; Miwa, 2021 ; Numata, 2021 ), aripiprazole ( Segnitz et al, 2009 ; Yoneyama et al, 2014 ; Crosby et al, 2021 ), low dose naltrexone ( Cabanas et al, 2021 ), ketogenic diet ( Cossington et al, 2019 ), ketamine ( Chang et al, 2009 ), vagal stimulation ( Clancy et al, 2014 ; Meneses et al, 2016 ; Rodriguez et al, 2020 ; Namgung et al, 2022 ), and noninvasive transcranial neurostimulation ( Gómez et al, 2021 ; Sabel et al, 2021 ; Workman et al, 2021 ) may be informative. Therapies that indirectly affect the innate CNS immune response, including staphylococcal vaccine ( Zachrisson et al, 2002 , 2004 ), Bacillus Calmette–Guérin (BCG) vaccine ( Blok et al, 2015 ; Sánchez-Ramón et al, 2018 ), rintatolimod ( Strayer et al, 2020 ) and stellate ganglion block should also be considered ( Lipov et al, 2020 ; Liu and Duricka, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Post-infectious syndromes also occur after other viral infections [25][26][27][28][29][30] and are known since decades. They partly result in myalgic encephalomyelitis/chronic fatigue syndrome (ME/CFS) [11,25,26,[30][31][32][33], which is closely connected to long COVID. Symptoms of long COVID range from fatigue, tiredness, muscle weakness, joint and muscle pain, cognitive impairments ('brain fog'), depression and anxiety, dyspnoea, chest pain and tightness, cough, loss of taste and smell, headache, cardiac symptoms, insomnia, diarrhoea and more [1,2,11,13,14,19,[34][35][36].…”
Section: Introductionmentioning
confidence: 99%
“…Animal studies have demonstrated attenuation of acute lung injury following this approach [38]. Similarly, human long COVID-19 symptoms have been significantly improved after a similar intervention [39] . These observations may indicate a central theme across these disease states as applied to COVID-19 that the central stress response systems with LC_NE/SNS axis overactivation is a main driver for the immunopathology observed in COVID-19 pneumonia [31] [33].…”
Section: Sars-cov2 Imbalance Central Stress Response System In Vulner...mentioning
confidence: 96%